Komitmen Organisasi Sebagai Variabel Pemediasi Ppengaruh Kepuasan Kerja Terhadap Kinerja Karyawan - Dijah Julindrastuti; Iman Karyadi (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
Employees are one of the company's most valuable assets that must be managed properly by the company in order to make an optimal contribution. Job satisfaction is one that must be considered because job satisfaction can affect the performance of employees. This research examines to determine whether organizational commitment as a mediating variable influences job satisfaction on employee performance. The population in this study were all non-educational employees at UWKS Surabaya. The sample was determined using the convenience sampling method. The data analysis used in this study was Structural Equation Modeling (SEM) which was operated through the AMOS program. The results showed that job satisfaction has an effect on organizational commitment while organizational commitment has no effect on employee performance so that organizational commitment does not act as a mediating variable between job satisfaction and employee performance.